Improving Photocatalytic Hydrogen Production with Sol–Gel Prepared NiTiO₃/TiO₂ Composite - Alberto Bacilio Quispe Cohaila; Elisban Juani Sacari Sacari; Wilson Orlando Lanchipa Ramos; Hugo Benito Canahua Loza; Rocío María Tamayo Calderón; Jesús Plácido Medina Salas; Francisco Gamarra Gómez; Ramalinga Viswanathan Mangalaraja; Saravanan Rajendran (Energies)
This study presents a comprehensive investigation into the synthesis, characterization, and photocatalytic performance of NiTiO3/TiO2 nanocomposites for solar hydrogen production. Through a carefully optimized sol–gel method, we synthesized a heterojunction photocatalyst comprising 99.2% NiTiO3 and 0.8% anatase TiO2. Extensive characterization using XRD, Raman spectroscopy, FTIR, UV–visible spectroscopy, photoluminescence spectroscopy, and TEM revealed the formation of an intimate heterojunction between rhombohedral NiTiO3 and anatase TiO2. The nanocomposite demonstrated remarkable improvements in optical and electronic properties, including enhanced UV–visible light absorption and an 85% reduction in charge carrier recombination compared to pristine NiTiO3. Crystallite size analysis showed a reduction from 53.46 nm to 46.35 nm upon TiO2 incorporation, leading to increased surface area and active sites. High-resolution TEM confirmed the formation of well-defined interfaces between NiTiO3 and TiO2, with lattice fringes of 0.349 nm and 0.249 nm corresponding to their respective crystallographic planes. Under UV irradiation, the NiTiO3/TiO2 nanocomposite exhibited superior photocatalytic performance, achieving a hydrogen evolution rate of 9.74 μmol min−1, representing a 17.1% improvement over pristine NiTiO3. This enhancement is attributed to the synergistic effects of improved light absorption, reduced charge recombination, and efficient charge separation at the heterojunction interface. Our findings demonstrate the potential of NiTiO3/TiO2 nanocomposites as efficient photocatalysts for solar hydrogen production and contribute to the development of advanced materials for renewable energy applications.